IMPROVEMENT OF SOCIAL SKILL IN LEARNING SOCIAL SCIENCE USING STAD METHOD THROUGH LAPATAR MEDIA - Sinta Maria Dewi; Ayu Fitri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research aims to examine the learning activities of Social Studies students using the method of Student Teams Achievement Divisions (STAD) through Media Lapatar (Experimental research class V SDN Anggdita III Klari District Karawang Regency) to increase the social skills of the elementary school students. The population of this study is all students of SDN Anggadita III of the 2019/2020 school year. The sample in the study was V C class as an experimental class of 20 students and VB as a control class as much as 20 students. Data obtained through tests. Data analyzed with testT. Data analysis results show the social skills of experimental graders better than the control class.It is seen from the value of posttest social skill student class of experiments is 68.65 higher than the value of posttest social skills students in the control class is 45.9.The hypothesis calculation using test-t i.e. test paired sample T test and obtained at a significant level 0.05 indicates that the value of probability (significance) is 0.00. Because of the significance value, then Ho is rejected. This proves that the use of student teams achievement method divisions affect the social skills of grade V students at SDN Anggadita III